Detection of oral mucosal lesions by screening examinations - Torres, Sandra R; Souza, Natalia Tavares; Romañach, Mário JoséRomañach; Cantisano, Marilia Heffer; Luiz, Ronir Raggio; Cardoso, Abel Silveira (Journal of Oral Diagnosis, 2020)
Introduction: Studies on the prevalence of oral lesions are important to characterize their occurrence in a population. The understanding of epidemiologic aspects, etiology, natural history and risk factors related to oral pathological conditions are essential to primary prevention, early diagnosis and treatment. Objective: The aim of this study was to evaluate the prevalence of oral mucosal lesions (OML) detected during a prevention campaign in stomatology, considering clinical, demographic and social data. Materials and methods: The study was conducted with data collected from a prevention campaign in stomatology, in the state of Rio de Janeiro, Brazil. The individuals who agreed to participate in the campaign were clinically examined and answered a questionnaire with sociodemographic questions. The clinically detected OML were recorded for analysis. Results: In the three days of the campaign, 10144 individuals were evaluated. The age ranged from 0 to 96 years old, with a mean of 45.0 ± 18.4 years. Twenty two percent of the participants presented OML which required control or treatment. The most prevalent oral lesion was candidiasis (5.2 %), followed by reactive lesions (3.8%), developmental alterations (2.8%), aphthous ulceration (2.1%), conditions related to prosthesis (1.6%), leukoplakia (1.5%) and traumatic ulcers (1.4%). The prevalence of OML was higher among elderly individuals, and there were no differences between genders. Conclusion: Oral mucosa screenings are important to detect OML and to refer individuals for treatment. When oral exams are performed as part of a prevention campaign, they provide important epidemiological data.